Nebulized plasma‐activated water has an effective antimicrobial effect on medically relevant microbial species and maintains its physicochemical properties in tube lengths from 0.1 up to 1.0 m. Issue 11 (3rd August 2021) - Chiappim, William; Sampaio, Aline; Miranda, Felipe; Petraconi, Gilberto; da Silva Sobrinho, Argemiro; Cardoso, Paulo; Kostov, Konstantin; Koga‐Ito, Cristiane; Pessoa, Rodrigo
Abstract: This study applies a proof of concept for future applications in controlling the microbiota in tubes and tracheal appliances used in the respiratory tract. Therefore, the physical–chemical parameters of the plasma‐activated and nebulized water (NPAW) are measured in a nebulizer tube with different lengths between 0.1 and 3.0 m. The pH values and oxidation–reduction potential (ORP) do not change during nebulization of PAW over a 1.0 m tube. However, for longer lengths, there is an increase in pH and a decrease in ORP. At 3.0 m, the pH increases approximately 16% compared with the 1.0 m position with a 20% decrease in the ORP values. Hydrogen peroxide (H2 O2 ) measured quantitatively using test strips presents values between 0.5 and 2.0 mg/L for condensed NPAW in different tube lengths between 0.1 and 3.0 m, and maintains the approximate value of 2.0 mg/L in tubes up to 1.0 m, with a reduction proportional to the increase in the length of the tube. The antimicrobial efficacy of NPAW applied for 15 min shows the inactivation of Staphylococcus aureus and Escherichia coli but without significant inactivation of Candida albicans . Abstract : We present a study on nebulized plasma‐activated water (PAW). We show the antimicrobial effect of PAW at the nozzle of the nebulizer, and in a tube coupled at the nozzle with length up to 1.0 m where the physicochemical parameters of the PAW are preserved at the tube end.